2020
DOI: 10.1001/jama.2020.7580
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ticagrelor Monotherapy vs Ticagrelor With Aspirin on Major Bleeding and Cardiovascular Events in Patients With Acute Coronary Syndrome

Abstract: IMPORTANCE Discontinuing aspirin after short-term dual antiplatelet therapy (DAPT) was evaluated as a bleeding reduction strategy. However, the strategy of ticagrelor monotherapy has not been exclusively evaluated in patients with acute coronary syndromes (ACS). OBJECTIVE To determine whether switching to ticagrelor monotherapy after 3 months of DAPT reduces net adverse clinical events compared with ticagrelor-based 12-month DAPT in patients with ACS treated with drug-eluting stents. DESIGN, SETTING, AND PARTI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
419
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 403 publications
(472 citation statements)
references
References 29 publications
12
419
0
7
Order By: Relevance
“…The difference between the groups was mainly driven by a reduced risk of major bleeding in the ticagrelor monotherapy group (0.2% vs. 1.6%, HR, 0.13; 95% CI, 0.04–0.44; p=0.001). 62) The Comparison Between P2Y 12 Antagonist Monotherapy and Dual Antiplatelet Therapy After DES (SMART-CHOICE) trial compared clinical benefits of aspirin plus a P2Y 12 receptor inhibitor for 3 months and thereafter P2Y 12 receptor inhibitor alone or DAPT for 12 months in Korean patients treated with drug-eluting stent (DES) (n=2,993, 58.2% of patients with ACS). 63) There were no significant differences in all-cause death (1.4% vs. 1.2%, HR, 1.18; 95% CI, 0.63–2.21; p=0.61), MI (0.8% vs. 1.2%, HR, 0.66; 95% CI, 0.31–1.40, p=0.28), or stroke (0.8% vs. 0.3%, HR, 2.23; 95% CI, 0.78–6.43, p=0.14) between the two groups.…”
Section: Antiplatelet Therapy For Acute Myocardial Infarctionmentioning
confidence: 99%
“…The difference between the groups was mainly driven by a reduced risk of major bleeding in the ticagrelor monotherapy group (0.2% vs. 1.6%, HR, 0.13; 95% CI, 0.04–0.44; p=0.001). 62) The Comparison Between P2Y 12 Antagonist Monotherapy and Dual Antiplatelet Therapy After DES (SMART-CHOICE) trial compared clinical benefits of aspirin plus a P2Y 12 receptor inhibitor for 3 months and thereafter P2Y 12 receptor inhibitor alone or DAPT for 12 months in Korean patients treated with drug-eluting stent (DES) (n=2,993, 58.2% of patients with ACS). 63) There were no significant differences in all-cause death (1.4% vs. 1.2%, HR, 1.18; 95% CI, 0.63–2.21; p=0.61), MI (0.8% vs. 1.2%, HR, 0.66; 95% CI, 0.31–1.40, p=0.28), or stroke (0.8% vs. 0.3%, HR, 2.23; 95% CI, 0.78–6.43, p=0.14) between the two groups.…”
Section: Antiplatelet Therapy For Acute Myocardial Infarctionmentioning
confidence: 99%
“…Among the full-text articles, 3 non-randomized trials, 2 case studies, 1 meta-analysis, 1 post hoc analysis and 24 repeated studies were eliminated. Finally, only five trials [9][10][11][12][13] were included in this analysis, as shown in Fig. 1.…”
Section: Searched Outcomesmentioning
confidence: 99%
“…The incidence of major adverse cardiac and cerebrovascular events was not significantly different between the two groups (2.3 vs. 3.4%, HR 0.69, p = 0.09). The study concluded that ticagrelor monotherapy after 3 months of DAPT offered modest but significant reduction in composite of major bleeding and cardiovascular events at 1 year compared to 12 months of DAPT [ 22 ].…”
Section: Introductionmentioning
confidence: 99%